Information security behavior among employees from the Islamic perspective - Barzak, Omar Mokhles; Abdul Molok, Nurul Nuha; Talib, Shuhaili; Mahmud, Murni (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This paper discusses employees' information security behavior from the perspective of Islam and provides a behavioral framework that is developed based on the combination of Western contemporary studies and the Islamic principles. In particular, the framework is based on the categorizations of Muslims' behavior and the concepts of rewards and punishment in Islam which can be reflected in managing information security behavior among employees. The proposed framework defines the taxonomy of each categorized information security behavior that can give better understanding for academia and organizations. This taxonomy can be used to identify the influencing factor of each categorized information security behavior and the strategies to manage such behavior.